SEGREGATION, SEX, AND LIFE EXPECTANCY: SURVIVAL GAPS ACROSS TIME IN A SOUTHERN COMMUNITY FROM 1915 – 2015 - Osusky, Grace (East Carolina University)
While global life expectancy dramatically increased across the 20th century, these gains were not uniformly experienced across individuals and populations. Public health researchers, who have sought to better understand these life expectancy gaps, have demonstrated a clear relationship between chronic stress and a heightened risk of premature death due to health conditions tied to inflammation, obesity, and cardiovascular disease. Broadly speaking, chronic stress accelerates the biological clock, wearing down bodily systems such as immune and heart function. Therefore, individuals who experience a disproportionately high burden of social stress are expected to suffer from both poorer health outcomes across the life course and a lowered life expectancy. Consequently, health is increasingly recognized as being, in part, socially constructed. That is, adverse social conditions result in distinct lived experiences and resultant divergent health outcomes across individuals and groups. However, as social conditions improve, life expectancy gaps are expected to narrow in response. To examine this predicted relationship, I target demographic data sourced from death certificates (n=8,484) from a small southern town across a 100-year time period (1915-2015). During the first half of this dataset, Jim Crow laws (1877-1965) resulted in policies that limited access to medical care, education, and employment for African Americans. However, following civil rights legislation, segregation ended, allowing for more equal access to resources and opportunities tied to increasing quality of life. Nonetheless, there is very little primary research on life expectancy gaps in the early 20th century, with most research in the southern U.S. targeting the post-Jim Crow period. Therefore, this work seeks to fill this knowledge gap through a longitudinal analysis of the survival probability of individuals during and after segregation. Results from Cox Regression modeling in R reveal statistically significant associations between an individual's sex, race, and year of death with their age at death. At the beginning of the 20th century, there was a clear race-based rather than gender-based gap in life expectancy, with White individuals (during Jim Crow n=1438, post Jim Crow n=3094) living, on average, 10 years longer than Black individuals (during Jim Crow n=1693, post Jim Crow n=2259). However, following desegregation, while life expectancy increases for all groups, the race-based gap in life expectancy narrows with Black women, in particular, experiencing the most dramatic increase in age at death, surpassing that of White men (~69 to 67 years respectively). What is clear from our findings is that survival probability is malleable and influenced by social pressures present in a given time and place. Ultimately, this research highlights how the social environment, here shaped by legislative change, can positively, or negatively, impact a person's health and resultant life expectancy.
Keywords: Jim Crow; Social Determinants of Health; Stress; Legislative Change; Civil Rights Act; Demography; African Americans--Mortality--Southern States; African Americans--Legal status, laws, etc; Health status indicators--Southern States; Public health--Southern States; Life expectancy--Social aspects--Southern States; Race discrimination--Southern States